Street Art and a New Space of Democracy in Post-Soeharto Indonesia: Reading Anti-Tank Project posters - Minanto, Ali (UI Scholars Hub, 2024)
This article deals with the intertwine between street art and the practice of democracy in post-Soeharto Indonesia. It attempts to investigate the role of street art in the contemporary political landscape of Indonesia, especially two decades after the reformasi (reformation) movement. Reformasi, which was marked by the collapse of the New Order regime in 1998, is regarded as a turning point in Indonesia's democracy after 32 years of authoritarian government. Street art took a crucial part in that historic moment as a medium of protest. This study shows cases of the Anti-Tank Project, one of Yogyakarta’s street artists, posters with four prominent issues: human rights, gentrification, rotten politicians, and anti-corruption, which are pivotal issues in strengthening the democracy agenda in Indonesia. I argue Anti-Tank Project has a significant role in the production of a new space of democracy through his works. This article investigates 12 Anti-Tank posters by employing the Peircean semiotic perspective and analyzes them through theoretical and conceptual approaches, namely democracy and participation, relational aesthetics, new social movement, and alternative media.